REVEALING PROBLEMATICS AND TECHNIQUES OF TRANSLATING ARABIC LANGUAGE INTO INDONESIA LANGUAGE - Eka Safitri; Alkhowarizmi, Annas; Sa'dudin, Ihsan (Institut Agama Islam Pemalang (INSIP) Jawa Tengah, 2024)
This study is an effort to find techniques for the translation of the Arabic Language to the Indonesian Language. This learning is according to the problems of Arabic Language translators. As for the purpose this study is knowing about techniques to use effectively and make easier in Arabic Language translation. Other than that, this study discusses a problem translation of the Arabic Language. This study uses a translation theory to analyze with kind of theory about problems of Arabic Language translation so can disclose the way detail about technique translate of the Arabic Language. This discussion refers to any kind of problem such as problems of vocabulary, problem of grammar, a problem of phrases, and problems of context. The result of this discussion technique translation of the Arabic Language is the translator must understand additional knowledge to support the result of the translation. For example the sociocultural science from resource language (Arabic Language). The quality of the result of the translation is related to the quality of the translator and the result translation hasn’t betrayed resources of language along with adapting to a target of language.